1989
DOI: 10.1007/bf00200799
|View full text |Cite
|
Sign up to set email alerts
|

Processing of figure and background motion in the visual system of the fly

Abstract: Abstract. The visual system of the fly is able to extract different types of global retinal motion patterns as may be induced on the eyes during different flight maneuvers and to use this information to control visual orientation. The mechanisms underlying these tasks were analyzed by a combination of quantitative behavioral experiments on tethered flying flies (Musca domestica) and model simulations using different conditions of oscillatory large-field motion and rela-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 74 publications
0
53
0
1
Order By: Relevance
“…It is known that flies can discriminate prominent foreground objects from the visual background (Reichardt and Poggio, 1979;Egelhaaf, 1985;Reichardt et al, 1989) and tend to fixate large, vertical stripes in the foreground (Götz, 1980;Götz, 1987). For this reason, we tested our flies with combinations of foreground and background rotations during saccades, and found that none of these manipulations had any significant effect.…”
Section: On the Role Of Visual Feedback During Flightmentioning
confidence: 99%
“…It is known that flies can discriminate prominent foreground objects from the visual background (Reichardt and Poggio, 1979;Egelhaaf, 1985;Reichardt et al, 1989) and tend to fixate large, vertical stripes in the foreground (Götz, 1980;Götz, 1987). For this reason, we tested our flies with combinations of foreground and background rotations during saccades, and found that none of these manipulations had any significant effect.…”
Section: On the Role Of Visual Feedback During Flightmentioning
confidence: 99%
“…Consequently, the turning responses were concluded to be mediated mainly by the object detection system. On the level of the lobula plate the object detection system is supposed to be represented by the FD-cells (Egelhaaf 1985a, b, c;Egelhaaf et al 1988;Reichardt et al 1989). In the behavioural experiments of Kimmerle et al (1997), the object was positioned in the most sensitive part of the FD1b-cell's receptive ®eld.…”
Section: Identi®cation Of Cellsmentioning
confidence: 99%
“…FD-cells are output elements of the lobula plate and project into the lateral protocerebrum where they probably synapse on descending neurons. FD-cells have been suggested to play a crucial role in mediating object-directed turning responses (Egelhaaf 1985a,b,c;Egelhaaf et al 1988;Reichardt et al 1989;Hausen and Wehrhahn 1990). It has been suggested recently that, in addition to the FD-cells described by Egelhaaf (1985b), further types of¯y TCs exist which also exhibit small-®eld-tuning (Gauck and Borst 1999).…”
Section: Introductioǹmentioning
confidence: 99%
“…There is now good evidence that two parallel control systems are involved which differ in their sensitivity to the size of the moving stimulus (Geiger and N/issel 1982;G6tz 1983a;Heisenberg and Wolf 1984;Egelhaaf 1985a-c;Bausenwein et al 1986;Egelhaaf et al 1988;Egelhaaf 1989;Reichardt et al 1989;Hausen and Wehrhahn 1990). In the housefly Musca and blowfly Calliphora, the control system that mediates compensatory optomotor turning reactions ("large-field system") responds best to extended binocular stimulus patterns rotating around roughly the vertical axis of the animal.…”
Section: Introductionmentioning
confidence: 99%